The Economic Burden of Asthma in the United States, 2008–2013 - Nurmagambetov, Tursynbek; Kuwahara, Robin; Garbe, Paul (Annals of the American Thoracic Society, 2018)
Asthma is a chronic disease that affects quality of life, productivity at work and school, and healthcare use; and it can result in death. Measuring the current economic burden of asthma provides important information on the impact of asthma on society. This information can be used to make informed decisions about allocation of limited public health resources. In this paper, we provide a comprehensive approach to estimating the current prevalence, medical costs, cost of absenteeism (missed work and school days), and mortality attributable to asthma from a national perspective. In addition, we estimate the association of the incremental medical cost of asthma with several important factors, including race/ethnicity, education, poverty, and insurance status. The primary source of data was the 2008-2013 household component of the Medical Expenditure Panel Survey. We defined treated asthma as the presence of at least one medical or pharmaceutical encounter or claim associated with asthma. For the main analysis, we applied two-part regression models to estimate asthma-related annual per-person incremental medical costs and negative binomial models to estimate absenteeism associated with asthma. Of 213,994 people in the pooled sample, 10,237 persons had treated asthma (prevalence, 4.8%). The annual per-person incremental medical cost of asthma was $3,266 (in 2015 U.S. dollars), of which $1,830 was attributable to prescription medication, $640 to office visits, $529 to hospitalizations, $176 to hospital-based outpatient visits, and $105 to emergency room visits. For certain groups, the per-person incremental medical cost of asthma differed from that of the population average, namely $2,145 for uninsured persons and $3,581 for those living below the poverty line. During 2008-2013, asthma was responsible for $3 billion in losses due to missed work and school days, $29 billion due to asthma-related mortality, and $50.3 billion in medical costs. All combined, the total cost of asthma in the United States based on the pooled sample amounted to $81.9 billion in 2013. Asthma places a significant economic burden on the United States, with a total cost of asthma, including costs incurred by absenteeism and mortality, of $81.9 billion in 2013.